Double-Clad Bismuth-Doped Fiber with a Rectangular Inner Cladding for Laser Application - Alexander Vakhrushev; Andrey Umnikov; Sergey Alyshev; Aleksandr Khegai; Elena Firstova; Lyudmila Iskhakova; Aleksei Guryanov; Mikhail Melkumov; Sergei Firstov (Photonics, 2022)
In this paper, we report the latest research results on the fabrication of double-clad Bi-doped germanosilicate core fibers with a rectangular inner cladding design for improved laser performance in the near-IR spectral region. Detailed comparative analysis of the absorption characteristics of the Bi-doped fibers with a circular- and rectangular-shaped inner cladding was performed. A series of cladding-pumped, Bi-doped fiber lasers emitting near 1.46 µm was developed using the semiconductor’s multi-mode fiber-coupled laser diodes at <semantics>λ</semantics> = 808 nm. The peculiarities of the laser parameters of the fabricated active fibers with the double-clad design were thoroughly studied by analyzing the dependencies of the slope efficiency of the lasers, namely the pump power, active fiber length and core-to-inner-cladding area ratio. The obtained results show that the rectangular design provided enhanced cladding absorption and improvements in laser performance. In particular, we achieved maximal slope efficiencies of 5.5% and 4.3% for the absorbed pump power introduced into the inner cladding with cross-section areas of 80 × 80 µm<semantics>2</semantics> and 125 × 125 µm<semantics>2</semantics>, respectively. Multi-wavelength lasing operation in a free-running cavity due to a few modes’ propagation regimes was found using the Bi-doped fiber with an 80 × 80 µm<semantics>2</semantics> inner cladding.